All Days 1997
DOI: 10.2118/38618-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Borate-Crosslinked Gel Rheology Using Laboratory and Field Scale Fracturing Simulations

Abstract: Accurate rheological characterization of hydraulic fracturing fluids in a laboratory is extremely important prior to their use in the field. A borate-crosslinked Guar gel rheology study was performed to compare and evaluate laboratory measurements with a field-scale characterization of the gel. Field-scale fracturing operation was simulated by slot measurements at the Fracturing Fluid Characterization Facility (FFCF) of the University of Oklahoma and laboratory-scale simulations were obtained from viscometer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…On the other hand, the heat transfer coefficient of the guar slurry is similar to that of the water. 21 This similarity means that the heat transfer characteristics of the fracturing slurry can be satisfactorily estimated from that for the water. Therefore, the current practice of predicting the slurry heat transfer characteristics with water can be successfully continued without compromising the fluid performance under real conditions.…”
Section: -52mentioning
confidence: 95%
See 3 more Smart Citations
“…On the other hand, the heat transfer coefficient of the guar slurry is similar to that of the water. 21 This similarity means that the heat transfer characteristics of the fracturing slurry can be satisfactorily estimated from that for the water. Therefore, the current practice of predicting the slurry heat transfer characteristics with water can be successfully continued without compromising the fluid performance under real conditions.…”
Section: -52mentioning
confidence: 95%
“…The results, however, also showed that the viscometer values differ considerably from the HPS viscosities measured after shear conditioning through 3000 ft length of the coiled tubing. 21 This result implies that the crosslinked fluid may exhibit ideal fluid properties under laboratory conditions, but under actual field conditions its behavior may be completely different. 20 Hence the borate crosslinked fluid rheology must be determined under conditions that closely simulate pumping environment through the wellbore and therefore, the laboratory characterization must incorporate shear history simulations prior to the viscometric measurements.…”
Section: -32mentioning
confidence: 99%
See 2 more Smart Citations
“…Several papers have been written describing the adverse effect that pumping fracturing fluids at high shear rates has on fluid stability (Goel et al 1997;. Other papers have presented data on the adverse effects on fluid stability caused by pumping fracturing fluids at low rates through coiled tubing (Shah and Subramanian 1997), but little information is available on the adverse effects of pumping at high rates.…”
Section: Introductionmentioning
confidence: 99%